2015
DOI: 10.1002/adma.201405632
|View full text |Cite
|
Sign up to set email alerts
|

TiS3 Transistors with Tailored Morphology and Electrical Properties

Abstract: Control over the morphology of TiS3 is demonstrated by synthesizing 1D nanoribbons and 2D nanosheets. The nanosheets can be exfoliated down to a single layer. Through extensive characterization of the two morphologies, differences in the electronic properties are found and attributed to a higher density of sulphur vacancies in nanosheets, which, according to density functional theory calculations, leads to an n-type doping.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
300
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(318 citation statements)
references
References 43 publications
17
300
0
1
Order By: Relevance
“…Nevertheless, predicting mobility from theory provides valuable insight into the fundamental properties of materials. Recently, the anisotropic character of the carrier mobility in TiS 3 was also observed in an experimental study [21].…”
Section: Carrier Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, predicting mobility from theory provides valuable insight into the fundamental properties of materials. Recently, the anisotropic character of the carrier mobility in TiS 3 was also observed in an experimental study [21].…”
Section: Carrier Mobilitymentioning
confidence: 99%
“…A recent theoretical study reported that the carrier mobility in 2D monolayer TiS 3 is highly anisotropic, and the electron mobility along the b direction is of the order of 10 4 cm 2 V −1 s −1 [22]. The experimentally reported mobility of TiS 3 is of the order of 10 2 cm 2 V −1 s −1 for sheets and 10 0 cm 2 V −1 s −1 for ribbons [20,21]. The deviation between theoretical and experimental values stems from the fact that the TiS 3 materials in experiment are multilayers rather than a monolayer and that the presence of defects and a substrate in the experiment can affect the mobility to a large extent.…”
Section: Carrier Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent calculations show that the interlayer potential (45 meV/atom), is less than that of MoS2 (60 meV/atom) and therefore should allow for exfoliation of the bulk down to a single layer. 46 Indeed, the 10 nm 9 thickness barrier was recently overcome through control of the morphology of the bulk material to produce flakes instead of ribbons. The flakes, with lower aspect ratio, allow exfoliation down to a single layer.…”
Section: Isolation and Exfoliation Of Mx3 Crystalsmentioning
confidence: 99%
“…46,48 This robust quality is in direct contrast with the TMDC layered materials which vary greatly with thickness and strain [49][50][51] . Moreover, mobilities for TiS3 transistors have been predicted to reach as high as 10000 cm 2 /Vs for the high mobility axis 26 and simple transistors, with 52 and without optimizations 46 , have been fabricated with reported mobilities as high as 70 cm 2 /Vs. The range of band gaps spanned by the TMTCs also makes them well suited for photodetection.…”
Section: Introductionmentioning
confidence: 99%